Inducible Bronchus–Associated Lymphoid Tissue (iBALT) Attenuates Pulmonary Pathology in a Mouse Model of Allergic Airway Disease - Hwang, Ji Young; Silva-Sanchez, Aaron; Carragher, Damian M.; Garcia-Hernandez, Maria de la Luz; Rangel–Moreno, Javier; Randall, Troy D. (Frontiers in Immunology, 2020)
Inducible Bronchus Associated Lymphoid Tissue (iBALT) is an ectopic lymphoid tissue that develops in the early postnatal period and is associated with severe forms of chronic lung diseases, including chronic obstructive pulmonary disease, rheumatoid lung disease, hypersensitivity pneumonitis and asthma, suggesting that iBALT may exacerbate these clinical conditions by promoting larger or faster immune responses in the lung. However, despite the link between pulmonary pathology and iBALT formation, the role of iBALT in pathogenesis remains unknown. Here we tested whether the presence of iBALT in the lung prior to sensitization and challenge with a pulmonary allergen altered the biological outcome of disease. We found that the presence of iBALT did not exacerbate Th2 responses to pulmonary sensitization with ovalbumin, but rather reduced eosinophil recruitment, reduced goblet cell hyperplasia and reduced mucus production. The presence of iBALT did not alter Th2 priming, but instead altered the spatial distribution of T cells in the lung. These results suggest that the formation of iBALT and sequestration of effector T cells in the context of chronic pulmonary inflammation may be a mechanism by which the immune system attenuates pulmonary inflammation and prevents excessive pathology.